Intestinal Protozoan Infections in Cancer Patients Undergoing Chemotherapy in Shahrekord the Central Southwest of Iran in 2018 - Seyed Mahmood Banihashemi; Eissa Soleymani; Rahman Abdizadeh; Mousa Motavalli Haghi; Bahman Khalili (Shahrekord University of Medical Sciences, 2020)
Background and aims: Parasitic infections, especially opportunistic parasites, can cause serious problems for immunocompromised patients. In this regard, this study aimed to evaluate parasitic infections in cancer patients undergoing chemotherapy after referring to Kashani hospital of Shahrekord from January to May 2018.   Methods: In this cross-sectional descriptive study, 750 stool samples were collected from 250 cancer patients undergoing chemotherapy (three fecal samples from each patient) and sent to the Parasitology Laboratory of Shahrekord University of Medical Sciences. All samples were examined macroscopically and microscopically through the direct method and a specific acid-fast staining method. To confirm the microscopic results, DNA was extracted from isolated parasites and amplification was performed by the polymerase chain reaction with the specific primers on positive samples.   Results: In this study, 106 (42.4%) and 144 (57.6%) patients were males and females, respectively. In addition, 187 (74.8%) and 63 (25.2%) of them were living in urban and rural areas, respectively. In terms of the education level, most patients had a low level of literacy. Further, 12 (4.8%) patients were infected with intestinal parasites that including, 7 (2.8%), and 5 (2%) samples were infected with Blastocystis hominis and Giardia lamblia, respectively.   Conclusion: The results of this study showed that B. hominis and G. lamblia are the most prevalent parasites in cancer patients undergoing chemotherapy. Although the prevalence of intestinal parasites in cancer patients was low, these findings should not be contrary to the need for healthcare regarding the prevention of parasitic infections in cancer patients.